Assessment of the global digital elevation models ASTER and SRTM in Greece. Issue 338 (September 2014) - Ioannidis, C.; Xinogalas, E.; Soile, S.
Abstract : This study evaluates the height accuracy of the free to download global digital elevation models (DEMs): advanced spaceborne thermal emission and reflection radiometer (ASTER) global digital elevation model (GDEM) and shuttle radar topography mission (SRTM) for the area of Greece. The analysis is done in two ways; using control points with known elevation and accurate DEMs. Quantitative and qualitative assessments are made both for the whole country, and for specific regions (test sites). Using the DEMs of SRTM with coverage from 56°S to 60°N and ASTER GDEM with coverage from 83°S to 83°N, the elevation information is available to users free of charge almost worldwide. In the regions where both data sets exist, the question arises which one is best to use; the decision is based on a series of parameters, such as accuracy, homogeneity, reliability, completeness, performance of morphological features, as well as the purpose of the work for which the elevation information will be used. These parameters are reviewed and analysed using data covering Greece. The data come from various providers and varying formats. The evaluation of the results highlights the need for a 'fit for purpose' use of each of these DEMs, taking into consideration the implementation constraints (technical and qualitative specifications of each project), along with the usefulness of these DEMs for a wide range of applications.